Immersion, Identification, and the Iliad - Ready, Jonathan L. (Oxford University Press, 2023)
Immersion, Identification, and the Iliad explains why people care about this foundational epic poem and its characters. It represents the first book-length application to the Iliad of research in communications, literary studies, media studies, and psychology on how readers of a story or viewers of a play, movie, or television show find themselves immersed in the tale and identify with the characters. Immersed recipients get wrapped up in a narrative and the world it depicts and lose track to some degree of their real-world surroundings. Identification occurs when recipients interpret the storyworld from a character's perspective, feel emotions congruent with those of a character, and/or root for a character to succeed. This volume situates modern research on these experiences in relation to ancient criticism on how audiences react to narratives. It then offers close readings of select episodes and detailed analyses of recurring features to show how the Iliad immerses both ancient and modern recipients and encourages them to identify with its characters. Accessible to students and researchers, to those inside and outside of classical studies, this interdisciplinary project aligns research on the Iliad with contemporary approaches to storyworlds in a range of media. It thereby opens new frontiers in the study of ancient Greek literature and helps investigators of audience engagement from antiquity to the present contextualize and historicize their own work.